2016
DOI: 10.1542/peds.2015-1754
|View full text |Cite
|
Sign up to set email alerts
|

Rebound Growth of Infantile Hemangiomas After Propranolol Therapy

Abstract: Rebound growth occurred in 25% of patients, requiring modification of systemic therapy in 15%. Predictive factors for rebound growth included age of discontinuation, deep IH component, and female gender. Patients with these predictive factors may require a prolonged course of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
94
6
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 23 publications
3
94
6
7
Order By: Relevance
“…18 The rate of rebound growth (32%) was consistent with that of previous reports. 18,19 However, the proportion of patients who were judged as requiring retreatment in our study (24%) was higher than in the retrospective studies (15% 19 and 12% 18 of patients required retreatment or modification of systemic therapy) and the pivotal study (10% 13 of patients required retreatment). However, these studies were not restricted to high-risk IH patients only, who are more likely to require treatment.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…18 The rate of rebound growth (32%) was consistent with that of previous reports. 18,19 However, the proportion of patients who were judged as requiring retreatment in our study (24%) was higher than in the retrospective studies (15% 19 and 12% 18 of patients required retreatment or modification of systemic therapy) and the pivotal study (10% 13 of patients required retreatment). However, these studies were not restricted to high-risk IH patients only, who are more likely to require treatment.…”
Section: Discussioncontrasting
confidence: 71%
“…13 Therefore, we evaluated the efficacy and safety of oral propranolol in patients with high-risk IH when administered for a minimum of 6 months and up to a maximum of 12 months of age. Furthermore, because rebound growth is reported in ∼25% of patients after stopping propranolol, 18,19 the persistence of IH response and the efficacy of retreatment was evaluated along with the impact of treatment on parents' quality of life (QoL).…”
mentioning
confidence: 99%
“…The findings of Shah et al 10 confirm the findings of others, and expand our understanding of this phenomenon. Their finding of increased rebound in deep or mixed IH and segmental IH is consistent with other reports, [6][7][8] as is the increased risk of rebound observed in girls 2,[6][7][8] The aforementioned hemangioma subtypes may represent a unique subpopulation of IH programmed to proliferate longer.…”
supporting
confidence: 84%
“…11,12 In a series of IH with prolonged growth by Brandling-Bennett et al, 11 all 23 lesions were on the head and neck, another feature found in the current study; in that series, nearly 40% of IH involved the parotid gland, a detail not included in the current report. The data from Shah et al 10 expand the published observations on rebound as a function of duration of OP therapy and age at the time of discontinuation or taper. Several previous studies report a higher rebound rate with shorter durations of OP therapy, 2, 6, 13 although in others this association is less clear.…”
supporting
confidence: 65%
See 1 more Smart Citation